SIDE-CHAIN SPECIFICITY IN THE ENZYMATIC-SYNTHESIS OF PENICILLINS - Baldwin, J; Schofield, C; Smith, B (1990)
5-Carboxynaphth-1-oyl-, 4-carboxybenxoyl-,trans-5-carboxy-3-pentenoyl- and cis-5-carboxy-3-pentenoyl-L-cysteinyl-D-valine were shown to be converted by isopenicillin N synthetase to their corresponding penicillins in yields of 90%, 12%, 40% and 5%, respectively. © 1990.